THE INFLUENCE OF INTEGRITY AND ISLAMIC SELF-REGULATION TOWARD TRANSFORMATIONAL LEADERSHIP ON MANAGEMENT OF SHARIA ORGANIZATION - Wibowo, Ugung Dwi Ario (Psikoislamedia: Jurnal Psikologi, 2018)
The objective to be achieved in this research is to find how the influence of integrity to transformational leadership on management of sharia organization; the influence of islamic self- regulation toward transformational leadership on the management of sharia organizations; as well as the influence of Islamic self-integrity and self-regulation on transformational leadership on management of sharia organizations. The subject of research is the leader or managers of Baitul Maal wal Tanwiil (BMT) or sharia financial services cooperative in Banyumas, Central Java, Indonesia, which are 32 leaders. Criteria of the management are: occupy the element of leadership or have the role of managing people/leadership in job description and have subordinates in their work. Data were collected using questionnaires. The results showed that: there was a significant influenc of integrity toward transformational leadership; there was a significant infleunce of islamic self-regulation toward transformational leadership; and there was a significant influence of integrity and islamic self-regulation simultaneously toward transformational leadership.